An experimental and modeling study of CO2 solubility in a 2-amino-2-methyl-1-propanol (AMP) + N-methyl-2-pyrrolidone (NMP) solution. (16th January 2018) - Pakzad, Peyman; Mofarahi, Masoud; Izadpanah, Amir Abbas; Afkhamipour, Morteza; Lee, Chang-Ha
Graphical abstract: Highlights: New experimental data for CO2 solubility in AMP + NMP + H2 O system was presented. Experimental data predicted by modified Kent–Eisenberg and Deshmukh–Mather models. Clausius–Clapeyron equation was used for calculation of the absorption heat. Deshmukh–Mather model predicted the experimental data with an AARD% of 3.08. Abstract: In this study, an experimental setup based on the static-synthetic method was used to measure the new experimental data of CO2 solubility in an aqueous solution of 2-amino-2-methyl-1-propanol (AMP) + N-methyl-2-pyrrolidone (NMP) solution. For the static-synthetic method, the mass balance of compositions and the pressure–volume–temperature conditions were used for measuring the amount of absorbed CO2 by the AMP+NMP solution. The measurements were performed over a temperature range of 313.15–353.15 K, CO2 partial pressure up to 316.7 kPa, and in different concentrations of the AMP+NMP solution. Two models, modified Kent–Eisenberg, and Deshmukh–Mather, based on the empirical correlations and activity-fugacity approach, respectively, were used for the prediction of experimental data. The parameters of the equilibrium constants of the protonation and carbamate reactions for the modified Kent–Eisenberg model and the interaction parameters for Deshmukh–Mather model were obtained. For validation of our setup, a new set of experimental data for the solubility of CO2 in an aqueous solution of AMP, methyldiethanolamine (MDEA) and diethanolamine (DEA) were measured and compared with existing experimental data in the literature, and good results were obtained. The results of the modeling study showed that the Deshmukh–Mather model gave a better prediction of experimental CO2 loadings data than the modified Kent–Eisenberg. Also, the results showed that the solubility of CO2 in an aqueous solution of AMP+NMP increases as the CO2 partial pressure increases while the temperature decreases.